2007
DOI: 10.1002/anie.200701297
|View full text |Cite
|
Sign up to set email alerts
|

Thin, Conformal, and Continuous SnO2 Coatings on Three‐Dimensional Biosilica Templates through Hydroxy‐Group Amplification and Layer‐By‐Layer Alkoxide Deposition

Abstract: Appreciable effort is underway to develop robust protocols for synthesizing functional nanostructured assemblies. Desired characteristics for such protocols include precise control of structure (down to the nanoscale), versatile control of chemistry (for tailored functionality), and massively parallel assembly (for large-scale manufacturing). The precise, versatile, and scalable fabrication of functional nanostructured assemblies, particularly those with intricate 3D morphologies, remains a significant challen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 68 publications
(46 citation statements)
references
References 17 publications
0
46
0
Order By: Relevance
“…SnO 2 coatings required amplifi cation of surface hydroxyl groups on silica diatoms by a thin interlayer of acrylate functionalized with glucosamine, for improved adhesion of the conformal SnO 2 coating. [ 109 ] The silica scaffold can then be removed by etching with HF or hot NaOH or KOH solution. This was shown, for example in the case of porous carbon templated by diatomaceous earth, in a preparation involving sucrose and sulfuric acid as the carbon source.…”
Section: Biotemplatesmentioning
confidence: 99%
“…SnO 2 coatings required amplifi cation of surface hydroxyl groups on silica diatoms by a thin interlayer of acrylate functionalized with glucosamine, for improved adhesion of the conformal SnO 2 coating. [ 109 ] The silica scaffold can then be removed by etching with HF or hot NaOH or KOH solution. This was shown, for example in the case of porous carbon templated by diatomaceous earth, in a preparation involving sucrose and sulfuric acid as the carbon source.…”
Section: Biotemplatesmentioning
confidence: 99%
“…The random arrangement of granulard omains provided the appropriate hierarchical topography for attaining superhydrophobicity.M ore importantly,t he granulard omains deposited on the MF consists of residual chemicalr eactivity-which was furtherc onfirmed through standard FTIR analysis [45][46][47] as shown in Figure 1E.T he peaks at 1410 cm À1 and 1735 cm À1 , which are the characteristicsignatures for the symmetric deformation of CÀHb ond for b carbon of the vinyl group and the carbonyls tretching of the ester linkage, revealed the existence of residual acrylate groupsi nt he deposited nanocomplexes. This residual chemical reactivity allowed post covalentm odification of the nanocomplex coated MF with selected alkylamine to attain essential low surface energy in the material.A fter the post chemical modification of the residual acrylate moieties with octadecylamine (ODA), the IR peak intensity at 1410 cm À1 significantly depleted with respect to the normalized carbonyl stretching peak at 1735 cm À1 ,w hichu nambiguously indicated the successful post covalent modification of the material through1 ,4-conjugate addition reaction.…”
Section: Synthesis Of Chemically Reactive Melamine Foam (Smf) and Itsmentioning
confidence: 79%
“…The hydroxyl-rich diatom frustules were then subjected to an automated LBL surface sol-gel process [45] to decorate the frustules with a thin, iron oxide-bearing coating. In a typical surface sol-gel cycle, the surface modified diatom frustules were immersed in Fe(III) isopropoxide (0.01 M, Alfa Aesar) solution in anhydrous 2-propanol (99.8þ%, Acros Organics) for 10 min followed by vacuum filtration.…”
Section: Methodsmentioning
confidence: 99%
“…However, we have recently shown that the formation of a continuous surface sol-gelderived SnO 2 coating on diatom frustules required enrichment of the surface hydroxyl groups present on the native frustule surfaces. [45] In such prior work, surface hydroxyl amplification was accomplished through a straightforward, two-component, sequential, LBL-type method for fabricating hyperbranched multilayers that involved the repetitive Michael addition of polyfunctional amine-containing species to polyfunctional acrylates, followed by the final binding of a hydroxyl-rich amine (D-glucosamine). Subsequent use of the surface sol-gel process then yielded a thin ( 50 nm), conformal coating of nanocrystalline SnO 2 on diatom frustules that enabled a single diatom frustule to be used as a minimally-invasive, rapid, and sensitive NO gas detector.…”
mentioning
confidence: 99%